SMEs as victims of competition violations in the EU: an empirical investigation - Özbuğday, Fatih Cemil (Journal of Business Economics and Management, 2024)
This paper investigates the nature and extent of competition violations experienced by SMEs in the EU-27 countries. Using data from the Flash Eurobarometer 510 Survey, this study employs a Heckman sample selection model to correct for potential selection bias. The findings reveal that while most SMEs do not face significant competition problems, those that do mainly struggle with high prices and powerful suppliers imposing unfair conditions. Interestingly, SME size and age do not significantly affect exposure to antitrust offenses, but industry sector and geographical location do. The paper emphasizes the potential roles of SMEs in competition authorities’ market oversight activities, given their unique market position and ability to detect competition violations early. Finally, the article calls for continuous engagement with SMEs by policymakers, regulators, and competition authorities to improve market competition.